The Effectiveness of Police Roles in Addressing the Distribution of Alcoholic Beverages in Pematang Siantar City - Anggun Pasaribu; Sarles Gultom; Desy Kartika C. Sitepu (Academic Solution Publisher, 2024)
The issue of alcoholic beverages in Indonesia has become a serious social problem, as despite numerous cases of alcohol-related deaths, the consumption of alcoholic beverages continues to rise each year, where law enforcement and relevant authorities have made efforts to regulate and eradicate alcohol abuse by apprehending both sellers and consumers involved in the illegal alcohol trade, yet the business continues to thrive, prompting this study to examine the urgency of alcohol prohibition, the role of law enforcement in alcohol control in Pematang Siantar, and the challenges faced in eradicating alcoholic beverages, leading to the conclusion that alcohol prohibition is crucial due to its negative impacts on behavior, morality, religion, and health, as well as its contribution to high crime rates, while the police play a vital role in mitigating alcohol abuse through guidance, supervision, and regulatory control, although law enforcement efforts are hindered by resistance from business owners who oppose police raids, perceiving them as detrimental to their economic interests